Diversity and Abundance of Intertidal Rove Beetles (Coleoptera: Staphylinidae) in Bachok coast, Kelantan, Malaysia. - Abdullah, Fauziah (Malaysian Journal of Science, 2010)
A study on the fauna of intertidal rove beetles (Coleoptera:Staphylinidae) was conducted from 30th May to 7th June 2009 in the Bachok coast, Malaysia. Collections were conducted at seven beaches, namely Nipah Beach, Irama Beach, Melawi Beach, Tok Bali Beach, Tanjung Chap Beach, Kemasin Beach and Perupok Beach. A total of 885 intertidal rove beetles comprising 34 species were collected from all seven sites of the Bachok coastal area. There was low species richness (Margalef index: 4.857) and high diversity of intertidal rove beetles (Simpson index: 0.906). Five identified species are new records for the Bachok coast, namely, Paederus fuscipes, Gymnusa atra, Tetraticta potita, Anorylus insecatus and Paederus sondaicus. Twenty-six species identified to family level are probably new to science. This first study ever conducted at Pantai Bachok shows that Bachok coastal area has a high diversity of intertidal rove beetles.